2017
DOI: 10.1007/s00595-017-1536-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgery or stereotactic body radiotherapy for elderly stage I lung cancer? A propensity score matching analysis

Abstract: The outcomes of surgery and SBRT for elderly patients with the early stage NSCLC were roughly the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
3
14
0
2
Order By: Relevance
“…Histopathological confirmation of NSCLC in the SBRT arm varied widely, between 30% and 100%, with five studies reporting <75% of patients with a confirmed histopathological diagnosis. 7, 36, 37, 39, 42 It should be noted that two of these studies were the only publications that showed a trend of longer disease-free survival for SBRT than surgery. 7, 37…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological confirmation of NSCLC in the SBRT arm varied widely, between 30% and 100%, with five studies reporting <75% of patients with a confirmed histopathological diagnosis. 7, 36, 37, 39, 42 It should be noted that two of these studies were the only publications that showed a trend of longer disease-free survival for SBRT than surgery. 7, 37…”
Section: Discussionmentioning
confidence: 99%
“…The result of the same OS between surgery and SBRT for matched patients with early-stage NSCLC is consistent with the previous studies(18, 47) which suggests that the health patients may get the same survival bene t from the two treatments. What's more, we should note that a large number of studies did not completely get the histology proof of malignance (11,20,27,28,31,32,35,37,38,45,47). In our study, the pooled results showed SBRT had more balanced OS with surgery for the patients with histopathological con rmed NSCLC than those with clinical NSCLC irrespective of matching.…”
Section: Discussionmentioning
confidence: 55%
“…For patients 75 years or older, the 3-year OS was 78.0% (95% CI 62.0-88.0%) with a median age of 82 years in the present study. Miyazaki et al recently reported that SBRT treatment and surgery exhibit similar results for patients 80 years or older with Stage I NSCLC using propensity score matching [22]. Taremi et al reported results using SBRT for medically inoperable lung cancer regardless of pathological confirmation [23] and observed no significant differences in OS among patients with pathologically confirmed cancer.…”
Section: Discussionmentioning
confidence: 99%